Pediatric Dengue Encephalopathy: A Review - Ilham Setiorizaldi; Amandianti Arimbi Tedjaningrum; Cindy Grace Panggabean; Enjelina Nangin; Jeffrey Christian Mahardhika; Chandni P. Daryanani (Rumah Sakit Unggul Karsa Medika, 2022)
Dengue encephalopathy is a very common neurological complication of dengue fever. Dengue encephalopathy or dengue hemorrhagic fever (DHF) with Central Nervous System (CNS) involvement used to be considered a relatively rare condition. However, the number of cases reported in human studies were increasing every year. Many factors caused the encephalopathy dengue. Possible mechanisms are hepatic failure (hepatic encephalopathy), cerebral hypoperfusion (shock), cerebral edema (vascular leakage) electrolyte disturbances, and intracranial hemorrhage due to thrombocytopenia or coagulopathy, which are secondary mechanisms of hepatic failure. Computed Tomography (CT) scan or Magnetic Resonance Imaging (MRI) of brain can be done to make certain of the diagnosis. The results can suggest the presence of extensive involvement of the bilateral cerebellar region, brain stem, and thalamus along with peculiar rim enhancement. Treatment in Intensive Care Unit (ICU) with a multidisciplinary team is required due to the patients’ decreased level of consciousness, underlying problems of airway, breathing, and circulation, comorbidities, and considerations of specific etiology.